2018
DOI: 10.1111/1745-5871.12286
|View full text |Cite
|
Sign up to set email alerts
|

Organisational responses to climate change: do collaborative forums make a difference?

Abstract: Innovative and effective responses to climate change require that we move beyond reliance on government to include organisations spanning different sectors, such as not‐for‐profit, private, and community groups. Interactions among these organisations in collaborative networks—or “forums”—may provide important mechanisms to successfully address climate change impacts. This paper investigates the relationships between organisational participation and involvement in forums and responses to climate change. Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Different types/sizes of organisations, working within different sectors, across different scales, and performing different roles and/or responsibilities, are all identified. Such diversity ensures that different values, interests and concerns are represented (Green et al 2018). Yet, despite the UK government clearly calling for a more bottom-up approach to adaptation in its NAP, we found little evidence that this rhetoric is consistently reflected in the documents the government has published on adaptation between 2006 and 2015.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different types/sizes of organisations, working within different sectors, across different scales, and performing different roles and/or responsibilities, are all identified. Such diversity ensures that different values, interests and concerns are represented (Green et al 2018). Yet, despite the UK government clearly calling for a more bottom-up approach to adaptation in its NAP, we found little evidence that this rhetoric is consistently reflected in the documents the government has published on adaptation between 2006 and 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Tompkins et al 2010). This is concerning because as Green et al (2018) have found, it is crucial to involve a wide diversity of actors with different issues, from different sectors, working across different scales, to ensure different values, interests and concerns are represented in efforts to tackle climate change. How to do this is not always clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may perceive sustainability issues as a low priority within their organisations and leverage the knowledge and discussions from interorganisational collaborations to influence decision-makers (Gustavsson, 2008). This enables them to strengthen their position and transform their home organisations (see also Green et al, 2018). While studies on corporate social responsibility communication in private organisations show similar struggles for decision-influencers to gain legitimacy and influence their organisations toward sustainability (Christensen et al, 2015), there are limited investigations into the external influence interor-ganisational collaborations may have in this regard.…”
Section: Collaboration Values For Participating Membersmentioning
confidence: 99%